2016
DOI: 10.1111/eva.12395
|View full text |Cite
|
Sign up to set email alerts
|

Has Scots pine (Pinus sylvestris) co‐evolved with Dothistroma septosporum in Scotland? Evidence for spatial heterogeneity in the susceptibility of native provenances

Abstract: Spatial heterogeneity in pathogen pressure leads to genetic variation in, and evolution of, disease‐related traits among host populations. In contrast, hosts are expected to be highly susceptible to exotic pathogens as there has been no evolution of defence responses. Host response to pathogens can therefore be an indicator of a novel or endemic pathosystem. Currently, the most significant threat to native British Scots pine (Pinus sylvestris) forests is Dothistroma needle blight (DNB) caused by the foliar pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Circumstantial evidence that D. septosporum has had a long‐term endemic presence in the Caledonian pine populations comes from studies of geographic variation in their DNB susceptibility. Pine populations from areas of high rainfall, where conditions are most favourable to D. septosporum , show significantly lower susceptibility than those in low rainfall areas, the pattern expected under long‐term co‐evolution (Perry, Brown, Cavers, Cottrell, & Ennos, ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Circumstantial evidence that D. septosporum has had a long‐term endemic presence in the Caledonian pine populations comes from studies of geographic variation in their DNB susceptibility. Pine populations from areas of high rainfall, where conditions are most favourable to D. septosporum , show significantly lower susceptibility than those in low rainfall areas, the pattern expected under long‐term co‐evolution (Perry, Brown, Cavers, Cottrell, & Ennos, ).…”
Section: Discussionmentioning
confidence: 88%
“…Analysis of the outcome of natural inoculations by the SR race present at Torrs Warren showed high genetic variation for susceptibility both within and among populations of Caledonian pine (Perry, Brown et al., ). Thus, although SR is likely to cause some damage to Caledonian pine populations, this could be mitigated if populations are able to naturally regenerate, allowing the evolution of greater resistance to SR by natural selection (Cavers & Cottrell, ).…”
Section: Discussionmentioning
confidence: 99%
“…), and populations from environments with greater climatic suitability for disease outbreaks are generally less susceptible to the native pathogens. Such trends have been reported previously in E. globulus (Hamilton et al ., ) and other forest trees (Ades et al ., ; Perry et al ., ). In E. globulus , physiological tolerance (Park, ) and disease risk modelling (Pinkard et al ., ) suggest that the probability of infection by TLD will increase with increasing temperature and precipitation in the near‐coastal region of southeastern Australia, which E. globulus inhabits.…”
Section: Discussionmentioning
confidence: 97%
“…This implies that under favourable conditions this host could be infected by the pathogen. Investigations on the impact of DNB on P. sylvestris revealed that there is high intraspecific variability of P. sylvestris in Europe and that susceptibility of the host to the pathogen varies between individuals (Perry et al ., ,b) and this could also influence the potential importance of L. acicola . Unusually high humidity associated with climate change could increase pathogen pressure on P. sylvestris (Perry et al ., ) and the single incidences in Europe should carefully be monitored.…”
Section: Host Range Host Susceptibility and Geographic Distributionmentioning
confidence: 99%
“…Investigations on the impact of DNB on P. sylvestris revealed that there is high intraspecific variability of P. sylvestris in Europe and that susceptibility of the host to the pathogen varies between individuals (Perry et al ., ,b) and this could also influence the potential importance of L. acicola . Unusually high humidity associated with climate change could increase pathogen pressure on P. sylvestris (Perry et al ., ) and the single incidences in Europe should carefully be monitored. Caution must also be taken when planting susceptible exotic hosts alongside native forests, as this could influence the vulnerability of native forests (Piotrowska et al ., ).…”
Section: Host Range Host Susceptibility and Geographic Distributionmentioning
confidence: 99%